Surgical audit of current management practices of ileal perforations presenting in a tertiary care institute of North India - Dalal, Satish; Singh, Mahavir; Kumar, Dinesh; Saharan, Amandeep; Bhatia, Chiesel (International Surgery Journal, 2017)
Background: Small bowel perforation is one of the commonest causes of abdominal emergency in India and other tropical countries mostly due to high incidence of enteric fever and tuberculosis. Surgical approach to these patients is standard but the choice of procedure continues to be debated. It is very important to find the appropriate management of these patients to reduce high mortality and morbidity. Methods: This prospective study on 50 patients of perforation peritonitis with small bowel perforation. After initial resuscitation with intravenous fluids and antibiotics surgery was done by midline incision and three modalities of surgical techniques were compared i.e. primary closure of perforation, resection and anastomosis and ileostomy depending upon the general condition of patient and local condition of gut. Results: Out of 50 patients, ten underwent primary repair of perforation, four patients were managed with ileal resection and end to end anastomosis and rest 36 patient required faecal diversion in form of ileostomy. Two patients expired in post-operative period that were cases of abdominal tuberculosis. Conclusion: Primary closure of perforation is preferable in patients with single small perforation with healthy surrounding bowel. Resection anastomosis is advocated in multiple perforations of any size with localized peritonitis of diseased segment pertaining to good general condition of patient. Ileostomy is lifesaving procedure particularly in patients of fulminant enteritis and peritonitis of long duration with associated co-morbidities but requires second surgery for closure.